A new species of the genus Tameothrips Bhatti (Thysanoptera: Thripidae) with four new records of thrips from India - Tyagi, Kaomud; Kumar, Vikas; Chauhan, Neena (Zootaxa, 2015)
A new thrips species of the grass-inhabiting Anaphothrips genus-group, Tameothrips arundo sp. n., is described from specimens collected on Arundo donax (Poaceae) from high altitude in Himachal Pradesh State of India. Four species of thrips in two subfamilies of family Thripidae are also reported for the first time from India, all of them well outside their known range: Helionothrips aino Ishida and Panchaetothrips noxius Priesner in the Panchaetothripinae, and Parabaliothrips takahashii Priesner and Scirtothrips kenyensis Mound in the Thripinae. This is the first record of Parabaliothrips Priesner from India. Diagnostic features and data on material studied for these species are provided.